Unlocking Success: Human Resource Management for Startupreneur - Jaan; Isabella Maria; Mia (Startupreneur Business Digital (SABDA Journal), 2024)
The purpose of this study is to find out how Human Resource Management (SDM) helps startupreneurs succeed. The study takes a qualitative approach, doing a thorough literature assessment of SDM practices pertinent to the startup setting, considering the background that startupreneurs face in managing human resources in a dynamic business environment. The research finds SDM best practices and methods that can support startupreneurs in their long-term success through a thorough examination of academic literature, industry reports, and relevant case studies. The findings of the research emphasize how crucial it is to choose and recruit carefully to draw in the greatest candidates, foster an innovative culture within the company, implement adaptive performance management, and produce creative leaders. Startupreneurs can enhance their business sustainability, promote growth, and optimize organizational performance by proficiently grasping and employing these SDM approaches. To sum up, SDM management is not just an administrative duty; it is also essential for startup entrepreneurs to overcome obstacles and thrive in a cutthroat industry.